2020
DOI: 10.5694/mja2.50472
|View full text |Cite
|
Sign up to set email alerts
|

Advances in type 2 diabetes therapy: a focus on cardiovascular and renal outcomes

Abstract: Summary Treatment options for type 2 diabetes have expanded. While metformin remains the first line treatment in most cases, choices for second line treatment now extend beyond sulfonylureas and include the sodium–glucose cotransporter 2 (SGLT2) inhibitors, glucagon‐like peptide 1 (GLP1) receptor agonists, and dipeptidyl peptidase 4 (DPP4) inhibitors. SGLT2 inhibitors are recommended for people with atherosclerotic cardiovascular disease, heart failure or kidney disease. Diabetic ketoacidosis is an uncommon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
1
8
0
1
Order By: Relevance
“…It was found that patients using DDP4 inhibitor-metformin compared to the sulfonylurea-metformin combination reported lower hospital visits. The reason for these findings might be due to reduced incidence of hypoglycemia with DDP4 inhibitor and their improved glycemic control leading to fewer risks of emergency conditions like diabetic ketoacidosis [ 24 , 26 29 ]. Combination of SU or DPP-4 inhibitors were prescribed more to the patients with worse comorbidities than control group (G1) metformin only.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that patients using DDP4 inhibitor-metformin compared to the sulfonylurea-metformin combination reported lower hospital visits. The reason for these findings might be due to reduced incidence of hypoglycemia with DDP4 inhibitor and their improved glycemic control leading to fewer risks of emergency conditions like diabetic ketoacidosis [ 24 , 26 29 ]. Combination of SU or DPP-4 inhibitors were prescribed more to the patients with worse comorbidities than control group (G1) metformin only.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown glucose lowering benefits of exenatide‐LAR 10,24–27 . Recent trials using GLP‐1 receptor agonists have shown both glucose‐lowering and added CVD protection 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown glucose lowering benefits of exenatide-LAR. 10,[24][25][26][27] Recent trials using GLP-1 receptor agonists have shown both glucose-lowering and added CVD protection. 10 This study highlights the importance of a model of care that incorporates the use of one of these agents safely and effectively in a high-risk population.…”
Section: Comparison To Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…20213.2 EFEITOS DOS iSGLT-2 E DOS ANÁLOGOS DO GLP-1 NOS DESFECHOS CARDIOVASCULARES EM PACIENTES COM DM2Os iSGLT-2 são medicamentos antidiabetogênicos, cujo mecanismo de ação consiste na inibição da reabsorção de glicose e de sódio no túbulo contorcido proximal renal, o que acarreta em glicosúria e em natriurese, como supracitado. Possuem como principais representantes a Dapagliflozina, nas dosagens de 5 a 10 mg e a Empagliflozina, em doses de 10 a 25 mg. São administrados por via oral, sendo capazes de reduzir a HbA1c em torno de 0,5% a 1%(LIBIANTO R, et al, 2020). Além disso, raramente induzem hipoglicemia e o seu uso proporciona melhora nos valores da glicose sérica, da pressão arterial, do peso corporal e da albuminúria, ao reduzirem os volumes plasmático e pressórico(RODRIGUES LL, et al, 2020).…”
unclassified